Use of Self-Reported Adherence and Keeping Clinic Appointments as Predictors of Viremia in Routine HIV Care in the Gambia. (July 2015) - Peterson, Kevin; Menten, Joris; Peterson, Ingrid; Togun, Toyin; Okomo, Uduak; Oko, Francis; Corrah, Tumani; Jaye, Assan; Colebunders, Robert
We followed 205 HIV-infected adults on antiretroviral therapy for at least 12 weeks in a Gambian clinic, where routine viral load monitoring was performed. The 1- and 4-week self-reported adherence and timeliness in keeping to scheduled appointments were recorded at each visit. Seventy patients had measurable viremia between the 12th week and the 3rd year of therapy. Survival analysis of the first detectable viral load on therapy demonstrated an association with 4-week (hazard ratio [HR] 2.6, 95% confidence interval [CI] 1.5-4.3, P = .001) and 1-week (HR 1.9, 95% CI 1.1-3.3, P = .024) self-reported suboptimal adherence and with 1 to 15 days of late presentation for appointments (HR 1.6-1.8, P .027-.109). In a multiple regression model, only 4-week self-reported adherence remained as a significant predictor of viremia.